Property Valuation and Sensitivity Analysis: Does Increased Disclosure Decrease Uncertainty? - Laakso, Roni (Nordic Journal of Surveying and Real Estate Research, 2018)
It has been suggested that one of the reasons for the persistence of the NAV discount phenomenon is that investors simply do not trust the disclosed property values of listed real estate companies. The purpose of the study is to find out whether investors trust reported fair values of investment properties more when corporations support the provided valuations with a sensitivity analysis. A sample of 102 European publicly listed real estate companies is used to conduct the empirical study. The study is based on a regression model which analyses the relationships between the disclosed amount of investment properties and the market value of equity. Data on the amount of investment properties held by the sample companies is collected from annual reports for fiscal year 2012. The study utilizes disclosures mandated by International Financial Reporting Standard IAS 40 which requires companies to disclose the methodology used to value investment properties. Additional data needed for the regression model is collected from the Thomson Datastream and Thomson Worldscope databases. Results of the empirical study support the research hypothesis, i.e. property values that are supported by sensitivity analyses are perceived by financial markets as more value relevant than properties for which no such analysis is provided.